Studi Fisika Tanah Pada Sistem Agroforestri Untuk Meningkatkan Retensi Air Di Tanah - Waruwu, Asdita; Lase, Septiani (CV. SINAR HOWUHOWU, 2024)
This research aims to understand how the physical characteristics of soil in agroforestry systems can influence water retention. Agroforestry, which combines trees or woody plants with agricultural crops, has the potential to increase soil texture, porosity, water capacity, as well as optimize soil infiltration and drainage. This study was carried out on agroforestry land combined with various types of trees and agricultural plants to evaluate soil physical changes that play a role in increasing water retention capacity. The research results show that agroforestry can increase water retention through changes in soil structure and better porosity. This study concludes that implementing an optimal agroforestry system can play an important role in maintaining soil moisture and increasing the sustainability of land productivity.